Estrategias lúdicas en el desarrollo del pensamiento lógico matemático de los niños y niñas de preparatoria de la escuela “Heriberto González” de la parroquia Bilován, cantón San Miguel período lectivo 2017-2018. - Quilligana Reinozo, Irma Liliana (2019)
The objective of this research work is to strengthen the development of mathematical logical thinking through the application of play strategies during the 2017-2018 school year of high school boys and girls of the "Heriberto González" school in Bilován parish, San Miguel Canton, Bolívar Province, the applied ludic tool was a guide of activities adapted to promote the development of logical thinking, the research methodology was based on a mixed, qualitative-quantitative approach, with a descriptive scope, evaluating 10 children and girls through surveys prepared by experts to diagnose their knowledge about playful strategies, applied to their teacher. With this approach to action research, the aim was to analyze the feasibility of applying a guide developed specifically for children in the study developed as an example of checking the effectiveness of a playful and globalized methodology for teaching learning and development of logical thinking in Early Childhood Education. An evaluation was made before and after the application of this guide, showing as a result an increase in the capacity for identification and resolution of logical problems, thus proving the hypothesis: "The use of appropriate play strategies enhances the development of the logical thinking of the students. high school boys and girls of the school "Heriberto González" Keywords: Strengthen, learning, playful, logical thinking, strategies, capacity